Needs of caregivers of youth enrolled in a statewide system of care: A latent class analysis. (April 2023) - Schreier, Alayna; Stenersen, Madeline R.; Strambler, Michael J.; Marshall, Tim; Bracey, Jeana; Kaufman, Joy S.
Highlights: Little is known about how caregiver-specific needs may impact use of and engagement with care coordination and subsequent youth and family outcomes in behavioral health systems of care. Latent class analysis identified four qualitatively different classes of caregivers including basic needs, physical needs, no needs and mental health/trauma needs. Class membership was associated with aspects of care delivery and with caregiver ratings of strain at follow-up. Assessing caregiver needs at presentation to care can provide direction for care coordinators to more directly target areas of family need through wraparound and individualize services. Abstract: Objective: Systems of care (SOC) provide a coordinated array of services to youth with serious emotional and behavioral problems and their families. Little is known about what caregiver-specific needs at presentation to care may contribute to use of and engagement with care coordination and subsequent youth and family outcomes. This study aimed to determine latent classes of youth enrolled in wraparound care coordination within a statewide SOC based on caregiver needs impacting youth functioning and identify the relationship between class membership and characteristics of participation in Child and Family Team meetings (CFTs) and mental health outcomes at six-month follow-up. Method: Participants were 703 youth ( Mage = 11.21, SD = 3.67) and their caregivers that had information about caregiver needs and received a six-month follow-up assessment. Latent class analysis determined latent classes of families based on caregiver service needs at presentation to care, and differences in participation in care coordination and youth outcomes at 6-month follow up based on class membership was examined. Results: Results indicated four classes of caregiversPhysical Health Needs, No Needs, Basic Needs, and Mental Health/Trauma Needs. Class membership was associated with size of the CFT, number of CFTs attended by the youth, percentage of CFTs with a natural support present, and percentage of CFTs that occurred in the family's home. Class membership was associated with caregiver ratings of objective strain at 6-month follow-up. Conclusion: Assessing caregiver needs at presentation to care can provide direction for care coordinators to more directly target areas of family need through wraparound and individualize services.